Do Older Indonesian with Chronic Disease Still Be Able to Engage in an Activity and Feel Happy? - Santi SULANDARI; Afrilin Dewi PURNAMA; Mei WIJAYANTI; Fitriana Dwi HASTUTI; Permata Ashfi RAIHANA (Prizren Social Science Journal)
This study aimed to understand what activities could be done by older Indonesian who are physically sick and how those activities can make them feel happy. It was a qualitative study conducted in the Surakarta, Central Java, Indonesia. A total of 6 older people aged >60 years and suffering from the chronic disease were selected for this study. The data were collected by an in-depth interview. The data were analyzed using thematic analysis with the help of the NVivo 12 QSR program. Older people with chronic disease were still able to be active in worship, socializing with the surrounding environment, working, doing the daily chores, and doing older people gymnastic. The benefit of staying engaged in the activity, including the ability to feel happy, be motivated to get a reward, exchange ideas, and share experience, help others, be calm, and have good health. This study emphasized the importance of being engaged in activities for older people to achieve happiness even though there had poor health status.